2004
DOI: 10.1163/156853904772746574
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variation in the Strength of Territory Defense in Male Song Sparrows: Correlates of Age, Territory Tenure, and Neighbor Aggressiveness

Abstract: In many species, the ability to defend a territory is essential for a male to obtain any reproductive success at all, and even among territorial individuals, variation in the strength of territory defense could have a significant impact on how much reproductive success is obtained. Previous studies have documented consistent individual differences in the vigor with which male song sparrows (Melospiza melodia) defend their territories, as measured by the strength of their reactions to territorial intrusions sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
63
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 22 publications
8
63
0
Order By: Relevance
“…In other words, if male song increases primarily as a result of territorial defense, then seasonal song activity should be positively correlated with the territorial intrusions and escalated aggressions (Chiver et al, 2015). Such results have been reported in Song sparrows (Hyman, Hughes, Searcy, & Nowicki, 2004;Nowicki, Searcy, Krueger, & Hughes, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…In other words, if male song increases primarily as a result of territorial defense, then seasonal song activity should be positively correlated with the territorial intrusions and escalated aggressions (Chiver et al, 2015). Such results have been reported in Song sparrows (Hyman, Hughes, Searcy, & Nowicki, 2004;Nowicki, Searcy, Krueger, & Hughes, 2002).…”
Section: Discussionsupporting
confidence: 64%
“…A number of studies have found that females preferentially mate with older males, possibly because older individuals have demonstrated viability (by surviving) and are often able to outcompete younger individuals (e.g. Hegyi et al, 2006;Hyman et al, 2004). The fact that older males produce more consistent songs suggests that females can gather information about the age of a male by assessing his vocal consistency and use this information to select potential mates.…”
Section: Functional (Behavioral) Studies Of Vocal Consistencymentioning
confidence: 99%
“…This pattern could represent an overall improvement of breeding skills (i.e. parental competence or obtaining high-quality territories) (Pä rt 2001a, b;Hyman et al 2004), increasing reproductive effort with age (Pä rt 1995), or heritable variation in survival (Mauck et al 2004). Although it is not well understood whether genes or experience contribute more to age-related patterns of reproductive success (Forslund & Pä rt 1995), theory suggests that genes for viability could be an indirect benefit of mating with older males (Kokko & Lindströ m 1996).…”
mentioning
confidence: 99%